OPTIMALISASI PENYUSUTAN EXIF METADATA DENGAN TEKNIK SUBSTITUSI NULL VALUE PADA KASUS KEAMANAN CITRA DIGITAL - Hendro Wijayanto; Iwan Ady Prabowo; Paulus Harsadi (STMIK Sinar Nusantara, 2018)
Data and information security technique is a way to keep an object confidential. eXchangable Image File Format (EXIF) Metadata is data information about digital image. In the digital forensic investigation, this is very useful for copyright security or safeguarding digital evidence. Steganography and cryptography techniques have been widely used to overcome these problem. However, from the research that has been done in terms of security EXIF of metadata digital image photography, there are still some weaknesses. Among them is the depreciation of the digital image size after decryption. Since the standard EXIF metadata treatmens released by JEIDA and CIPA have different characteristic with JFIF metadata. A null value will be deemed to be the content with a value of 1 in EXIF standard. While in JFIF metadata model, the value of null is considered to be worth 0 (zero). This is make the EXIF metadata security process is shrinking of -25,15% from the original size. With the optimizing null value before encryption, the same metadata will be obtained between original image and after decryption. The null value will be replaced with an empty string (it’s worth 1) before encryption. Results from the model obtained an average of -1,51% depreciation of the original digital image size.Therefore, this technique can optimize the digital image copyright protection.